ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2009-2011 - Zahrawani '; Amries Rusli Tanjung; Sem Paulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out empirical evidence of the affectof corporate governance mechanisms and firm size to earnings management in manufacturing companies. The variable examined in this research is institutional ownership, managerial ownership, proportion of independent board of commissioners, board of commissioner, audit committee, audit quality were measure by industry specialize audit firm, and firm size. Earning management measured with real earning management. The sample in this research are manufacturing companies which were listed in Indonesia Stock Exchange on period of 2009-2011. Total sample in this research are 43 companies that selected with purposive sampling method. The analysis method of this research using multiple regression and statistic descriptive. The results of this research indicate that proportion of independent board of commissioners and quality were measure by industry specialize audit firm, had significant influence to earning management. Whereas institutional ownership, managerial ownership, board of commissioner, audit committee and firm size had not significant influence to earning management.Keyword : Earnings Management, Institutional Ownership, ManagerialOwnership, Proportion of Independent Board of Commissioners, Board of Commissioner, Audit Committee, Audit Quality were measure by Industry Specialize Audit Firm, Firm Size